PENGARUH MODEL DISCOVERY TERHADAP KETERAMPILAN PROSES PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Apriana, Ema; Kresnadi, Hery; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to know the effect of discovery model on the process skills in thematic learning student fourth grade Elementary School in Pontianak. The experimental reseach method was used in this research. The form of the experimental research used was one group pretest postest design. Sample in this research weer students fourth grade which consisted of 28. Instrument gatherer data of student learning the test results obtained using measurement technique. The result of data analysis showed that mean score of student’s post-test based on t-test analysis on observation skilss, thitung of (7,35) and ttabel (1,703) then Ha accepted. On t-test analysis on hypothesis skills, thitung of (3,21), t-test analysis on instruction skilss (5,79), t-test analysis on communication skilss (1,96),)The result of effect size was 0,98 which mean hhig criteria on ES>0,7. So, it can be concluded there was a significant effect of using discovery model on the process skills of thematic learning student fourth grade Elementary School Keywords: Effect, Discovery Model, Process Skills